PENGARUH LEVERAGE, CAPITAL INTENSITY, SALES GROWTH, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE - Alifia Novanda Susan; Amir Faizal (Jurnal Ekonomi Trisakti, 2023)
The purpose of this research was to test and analyze the effect of leverage, capital intensity, sales growth, and institutional ownership on tax avoidance. The Effective Tax Rate (ETR) is used as a measure of tax avoidance. This study used a quantitative method with secondary research data obtained from the Indonesia Stock Exchange (IDX). The population of this study is energy sector companies (oil, gas & coal mining sub-sector) listed on the Indonesia Stock Exchange (IDX) in 2018-2021, by selecting the sample, namely the purposive sampling method, 16 companies were obtained with a 4-year research period and obtained a total of observations 64 research samples. The results of the analysis show that capital intensity, sales growth, and institutional ownership have a significant positive effect on tax avoidance. Meanwhile, leverage has no effect on tax avoidance.